2014
DOI: 10.1017/s1368980014001359
|View full text |Cite
|
Sign up to set email alerts
|

Adherence in a pragmatic randomized controlled trial on prophylactic iron supplementation during pregnancy in Maputo, Mozambique

Abstract: Objective: Assessing the level of adherence and its determinants is important in appraising the overall effectiveness of trials. The present study aimed to evaluate the extent of adherence and its determinants in a pragmatic randomized controlled trial of Fe prophylaxis during pregnancy in Maputo, Mozambique. Design: A pragmatic randomized controlled trial. Setting: Two health centres (1 o de Maio and Machava) in Maputo, Mozambique. Subjects: Pregnant women (≥12 weeks' gestation, ≥18 years old, non-high-risk p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 21 publications
1
14
2
Order By: Relevance
“…Women were asked some additional questions related to compliance. 20 Overall adherence to the trial (number of prenatal visits and intake of iron and folic acid tablets) was above the 50th centile. 20 …”
Section: Methodsmentioning
confidence: 93%
See 2 more Smart Citations
“…Women were asked some additional questions related to compliance. 20 Overall adherence to the trial (number of prenatal visits and intake of iron and folic acid tablets) was above the 50th centile. 20 …”
Section: Methodsmentioning
confidence: 93%
“…Both with regard to the compliance of nurses to the trial protocol and women's reported uptake of iron and folic acid tablets, we achieved adequate adherence. 17 18 20 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In pregnant Pakistani women with severe anemia thought to be caused primarily by iron deficiency, better than 85% adherence was required to achieve a 65% response to therapy, 47 but adherence to iron supplementation in pregnant Mozambican women has been reported as 67%. 48 Lack of adherence could be caused by both patient factors and increasingly frequent pharmacy stockouts in the study environment.…”
Section: Discussionmentioning
confidence: 99%
“…Forget fullness, vomiting, nausea, heartburn, and diarrheas were the main reasons of drug interruption [8–10]. In Mozambique, the iron sulfate adherence was 79% for having two or more visits, 53% for those having adequate prenatal care, and 67% for those who complete their intake of IFA tablets [11]. In Tigray, Ethiopia the rate of adherence to IFA supplementation was 37.2% [12] and Addis Ababa 60% [13].…”
Section: Introductionmentioning
confidence: 99%